2004
DOI: 10.1590/s0004-27302004000300016
|View full text |Cite
|
Sign up to set email alerts
|

Hipotireoidismo primário simulando volumoso macroadenoma hipofisário

Abstract: A 21-year-old woman complaining of 8-month amenorrhea associated to weight gain, galactorrhea and frequent headaches, presented for clinical evaluation; her laboratory tests were: TSH: 1192 mUI/ml (0.27-4.2); TT4: 1.0 microg/dl (4.4-11.4 l); TT3: 0.41 ng/ml (0.7-2.1); prolactin: 69.2 ng/ml (3-20) and a diagnosis of myxedema associated to galactorrhea was made. A hypothalamic-pituitary magnetic resonance imaging (MRI) showed a suprasellar and intrasellar mass lesion of 1.9 x 1.4 x 1.9 cm, determining compressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…In the literature, it has been suggested that in presence of markedly elevated TSH, absence of clinical features of hyperthyroidism, and low thyroid hormone values, one should suspect a diagnosis of pituitary enlargement secondary to primary hypothyroidism. [1,4] In this type of pituitary hyperplasia, the thyrotroph cells becoming enlarged by lack of negative feedback; indeed, the hormonal profile is usually straightforward, displaying unambiguous marked primary hypothyroidism with low circulating thyroid hormones and elevated TSH, easily reversible upon thyroid replacement. [5] Recognition of this entity is crucial (as in present case).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, it has been suggested that in presence of markedly elevated TSH, absence of clinical features of hyperthyroidism, and low thyroid hormone values, one should suspect a diagnosis of pituitary enlargement secondary to primary hypothyroidism. [1,4] In this type of pituitary hyperplasia, the thyrotroph cells becoming enlarged by lack of negative feedback; indeed, the hormonal profile is usually straightforward, displaying unambiguous marked primary hypothyroidism with low circulating thyroid hormones and elevated TSH, easily reversible upon thyroid replacement. [5] Recognition of this entity is crucial (as in present case).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]5] This case also illustrates the importance of determining thyroid function tests during the investigation of pituitary masses and avoiding the need to perform pituitary surgery. [4]…”
Section: Discussionmentioning
confidence: 99%
“…(11) Clinically the patients with pituitary hyperplasia can present with headache, visual symptoms and features of hypothyroidism. (1,3,7,14) It is important to understand that the headache may be due to hypothyroidism, although the exact underlying mechanism is not clear. (7) In many cases pituitary hyperplasias may be clinically silent and focal pituitary hyperplasia can be an incidental finding at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms are possibly involved in this occurrence: reduced secretion of some Prl inhibitory factors, increased secretion of TRH and enhanced pituitary sensitivity to tonic TRH secretion (1). Long lasting primary hypothyroidism can induce hyperplasia of TSH and Prl producing cells, causing a radiological image suggestive of a pituitary tumor (4)(5)(6)(7)(8).…”
Section: Persistence Of Hyperprolactinemia After Treatment Of Primarymentioning
confidence: 99%